1993
DOI: 10.1007/bf00195000
|View full text |Cite
|
Sign up to set email alerts
|

Irrigation response of Pistachio (Pistacia vera L.)

Abstract: Pistachio yields normally alternate between high and low values for consecutive years due to management and genetic effects. In this study, irrigated and nonirrigated treatments of old pistachio trees (Pistacia vera L.) were compared for 5 years from 1979 to 1983. Two irrigation treatments consisting of irrigation scheduling at 20-and 30-day interval were compared with the control treatment of no irrigation. Results showed that irrigation practice in pistachio orchards not only increased fruit yield, but also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
22
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 4 publications
3
22
1
Order By: Relevance
“…Goldhamer et al (1984) reported that water loss via ET in pistachio was 1017 mm during one irrigation season in California. Moreover, Kanber et al (1993) reported that water loss via ET in pistachio was 803 mm during one irrigation season in the region of southeastern Anatolia in Turkey. Differences in the reported levels of water loss via ET could be attributed to differences in soil and climate characteristics, and the irrigation methods used.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Goldhamer et al (1984) reported that water loss via ET in pistachio was 1017 mm during one irrigation season in California. Moreover, Kanber et al (1993) reported that water loss via ET in pistachio was 803 mm during one irrigation season in the region of southeastern Anatolia in Turkey. Differences in the reported levels of water loss via ET could be attributed to differences in soil and climate characteristics, and the irrigation methods used.…”
Section: Resultsmentioning
confidence: 99%
“…Irrigation water, rainfall, and moisture content were measured, and other components were assumed to be zero in the irrigation treatment due to the lack of rainfall (Kanber et al 1993).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This evolution lifted the curtain about the fact that pistachio tree water demand is not particularly low (Goldhammer et al, 1985) and that the potential evapotranspiration rate at the maximum seasonal evaporative demand is equal or exceeds that of many other deciduous species (Goldhammer et al, 1983). Kanber et al (1993) August. This assumption was in discordance with the negative balance between water needs and its availability since the majority of pistachio producing regions were suffering an alarming continuous depletion of their water reserves and could not always sustain the tree water requirements due to the scarcity of rain and the increasing competition for fresh water.…”
mentioning
confidence: 99%